Factors associated with tuberculosis drug resistance among presumptive multidrug resistance tuberculosis patients identified in a DRTB surveillance study in western Kenya - Albert Okumu; James Orwa; Ruth Sitati; Isaiah Omondi; Ben Odhiambo; Jeremiah Ogoro; George Oballa; Benjamin Ochieng; Steve Wandiga; Collins Ouma (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Multidrug-resistant tuberculosis (MDR-TB) is caused by M. tuberculosis (Mtb) with resistance to the first-line anti-TB medicines isoniazid (INH) and rifampicin (RIF). In Western Kenya, there is reported low prevalence of drug resistant strains among HIV tuberculosis patients, creating a need to determine factors associated with drug resistance patterns among presumptive MDR-TB patients. To determine factors associated with drug resistance patterns among presumptive MDR-TB patients in western Kenya. Three hundred and ninety (390) sputum sample isolates from among presumptive multidrug TB patients, were analyzed for TB drug resistance as per Ministry of Health (MoH) TB program diagnostic algorithm. Frequency and percentages were used to summarize categorical data while median and interquartile range (IQR) were used for continuous data. Multivariable logistic regression was carried out to identify factors associated with TB drug resistance. Out of 390 participants enrolled, 302/390 (77.4 %) were males, with a median age of 34 years. The HIV-infected were 118/390 (30.3 %). Samples included 322 (82.6 %) from presumptive patients, while 68/390 (17.4 %) were either lost to follow-up patients, failures to first-line treatment or newly diagnosed cases. A total of 64/390 (16.4 %) of the isolates had at least some form of drug resistance. Out of 390, 14/390 (3.6 %) had MDR, 12 (3.1 %) were RIF mono-resistance, 34 (8.7 %) had INH, while 4 (1 %) had ethambutol resistance. The category of previously treated patients (those who received or are currently on TB treatment) had a 70 % reduced likelihood of resistance (aOR: 0.30; 95 % CI: 0.13–0.70). In contrast, older age was associated with an increased likelihood of resistance to INH and RIF, with an adjusted odds ratio of 1.04 per year (95 % CI: 1.00–1.08). Prompt MDR-TB diagnosis is essential for appropriate patient care, management, and disease prevention and control. We recommend active surveillance on drug resistant TB in these regions to detect drug resistance patterns for rapid disease management.